(untitled) (Sains Humanika, 2020)
Based on demand for professional labor and the growing economy, the Technical and Vocational Education (TVET) system has been transformed into a system that works to develop and equip individuals with current technical skills based on industry demand. The government has undertaken various efforts to strengthen the field of Technical and Vocational Education. Among the efforts undertaken was the transformation of the Technical and Vocational Education and Training (TVET) system. Kurikulum Standard Kolej Vokasional (KSKV) syllabus has been introduced to guide the teaching process at Vocational College. The KSKV was developed based on the latest industry requirements under the National Occupational Skill Standard (NOSS). Jabatan Pembangunan Kemahiran (JPK) is responsible for ensuring that the skills provided to students meet NOSS standards. However, there are issues and challenges faced in implementing the transformation, which is the level of knowledge and technical skills proficiency that lecturers have that is an important aspect of enabling educators to cope with growing technology. In line with the latest technological advances and industry demands, the issue that has begun among lecturers is the preparation of lecturers in terms of knowledge and technical skills related to the latest technologies updated in KSKV. This will further impact the quality of teaching delivery delivered by lecturers at Vocational College. Finally, the latest technical skills are essential to enable the teaching process delivered by the lecturers to be mastered by the students and thus produce qualified Vocational College graduates according to the latest industry employment standards.